2014
DOI: 10.1159/000363242
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Sputum DNA Has NETosis Characteristics and Neutrophil Extracellular Trap Release Is Regulated by Macrophage Migration-Inhibitory Factor

Abstract: Neutrophils are the main proinflammatory cell type in chronically infected lungs of cystic fibrosis (CF) patients; however, they fail to effectively clear the colonizing pathogens. Here, we investigated the molecular composition of non-mucoid and mucoid Pseudomonas aeruginosa-induced neutrophil extracellular traps (NETs) in vitro and compared them to the DNA-protein complexes present in the CF sputum. The protein composition of P. aeruginosa-induced NET fragments revealed that irrespective of the inducing stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
165
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(180 citation statements)
references
References 39 publications
7
165
0
2
Order By: Relevance
“…Twenty-eight proteins were shared between the PAO1 strain and the PA14 strain (see Table S1 in the supplemental material). Many of these proteins were identical to previously reported NET-associated proteins, confirming the ability of PA14 to induce NETosis (13,24,25). To functionally prove that the cytotoxic PA14 strain induced NETosis, separate experiments were carried out with differentiated HL-60 cells (used as a model system for neutrophil responses) exposed to P. aeruginosa strain PA14 (MOI, 10) in the presence or absence of DNase I.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Twenty-eight proteins were shared between the PAO1 strain and the PA14 strain (see Table S1 in the supplemental material). Many of these proteins were identical to previously reported NET-associated proteins, confirming the ability of PA14 to induce NETosis (13,24,25). To functionally prove that the cytotoxic PA14 strain induced NETosis, separate experiments were carried out with differentiated HL-60 cells (used as a model system for neutrophil responses) exposed to P. aeruginosa strain PA14 (MOI, 10) in the presence or absence of DNase I.…”
Section: Resultssupporting
confidence: 80%
“…Whether NETs trap and kill P. aeruginosa is controversial. We, along with others, reported that the nonmucoid cystic fibrosis-derived P. aeruginosa strains were sensitive to NET trapping while the mucoid strains were resistant (13)(14)(15). In contrast, Parker et al reported that P. aeruginosa was not sensitive to NET-mediated killing (16).…”
mentioning
confidence: 59%
“…The CF lung is highly enriched in DNA derived primarily from neutrophils, including the presence of NETs that trap and kill bacteria (47,49,57). It was recently shown that P. aeruginosa lysates induce the H1-T6SS of kin cells but that the signal is unknown (51).…”
Section: Resultsmentioning
confidence: 99%
“…Given the abundance of nucleic acids in NETs, the induction of autoantibodies by NETosis is likely to be facilitated by TLR 7/9-mediated B cell activation (27). While formation of NETs in the CF lung has been appreciated as both an antibacterial defense mechanism and a contributor to proteaseinduced lung damage (10,(28)(29)(30), the role of NETosis in CF autoimmunity has not been studied.…”
Section: Introductionmentioning
confidence: 99%